2017
DOI: 10.1556/0806.45.2017.046
|View full text |Cite
|
Sign up to set email alerts
|

Effect of fertilization on the NPK uptake of different maize (Zea mays L.) genotypes

Abstract: In 2013 and 2014, the N, P and K contents of the aboveground phytomass and grain yield of maize hybrids (P 9494, SY Afinity) were examined, as well as the different amounts of N, P and K (kg ha -1 ) uptake at different nutrient levels (control, N 90 + PK, N 150 + PK), on calcareous chernozem soil in Eastern Hungary (47°33' N, 21°27' E). Our experimental findings proved that as a result of fertilization, the macronutrient (N, P, K) content of the maize hybrids significantly increased in both years in the vegeta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 27 publications
1
6
0
Order By: Relevance
“…The uptake of nutrient (N/ P/ K) and grain yield both were significantly ( p ≤ 0.05) affected by varied NPK levels and/or nutrient omission. Increasing doses of NPK up to 125% of RDF significantly ( p ≤ 0.05) increased the uptake of these macronutrients in maize grain, which is also supported by the results of other maize research [39]. Application of 125% RDF might have caused higher nutrient concentration in maize grain, and for the same reason, unlike for the higher doses of NPK (150% RDF), the dilution effect of nutrients was not witnessed in grain [40].…”
Section: Discussionsupporting
confidence: 76%
“…The uptake of nutrient (N/ P/ K) and grain yield both were significantly ( p ≤ 0.05) affected by varied NPK levels and/or nutrient omission. Increasing doses of NPK up to 125% of RDF significantly ( p ≤ 0.05) increased the uptake of these macronutrients in maize grain, which is also supported by the results of other maize research [39]. Application of 125% RDF might have caused higher nutrient concentration in maize grain, and for the same reason, unlike for the higher doses of NPK (150% RDF), the dilution effect of nutrients was not witnessed in grain [40].…”
Section: Discussionsupporting
confidence: 76%
“…These are heights that, due to various biotic and abiotic factors to which the maize plants are exposed, they do not usually reach [ 36 , 63 , 64 ]. In addition, the fertilizer dose, the genotype used and the harvest year are other factors that influence the adequate use of N, P and K fertilizer by maize plants [ 65 ].…”
Section: Resultsmentioning
confidence: 99%
“…The low ash, fat and protein contents in the chemical composition of corn starches, reported under the different fertilization schemes, indicate their high purity. In the literature, fertilization with N is reported as the main factor that determines the final concentration of grain protein [ 12 , 65 , 76 ]. In this sense, across all the treatments, a significant effect was found for treatments T7 and T3, which included chemical fertilizer, bioinoculants and/or organic matter within their formulation ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Mineral fertilizers cause an increase in production costs (Novais et al 2007). Generally, the research results indicated that different maize hybrids have a diverse yield compared with nitrogen fertilizer levels, and the Armagnac hybrid can be the maximum grain yield (Széles et al 2019;Pepó and Karancsi 2017). Superior hybrid recognition in the breeding plan is always difficult due to treatment changes in the target areas and the interaction of these changes with the genotypes studied.…”
Section: Introductionmentioning
confidence: 99%